PENINGKATAN PIGMEN WARNA DAN PERTUMBUHAN IKAN KOI (Cyprinus carpio) MELALUI PENGKAYAAN SUMBER KAROTENOID TEPUNG SPIRULINA - Putri Nur Hanida Rizky; Atika Marisa Halim; Nasuki Nasuki; M. Alfian Nur Rohman (Universitas Muhammadiyah Gresik, 2023)
Ornamental fish farming is one of the supporting sectors of the fishery community's economy. The increasing ornamental fish production in 2022 is more influenced by the increasing demand for native Indonesian ornamental fish in the world market. “KOI” is one of the iconic ornamental fish in Indonesia as the most widely produced ornamental fish in 2022. The existence of Spirulina as a natural source of carotenoids can replace the use of synthetic carotenoids, thereby saving production costs in aquaculture. This study was conducted to evaluate the effect of enriching carotenoid sources of Spirulina flour on color enhancement and growth of koi fish (Cyprinus carpio). 40 koi fish (Cyprinus carpio) were given different feed treatments. P0 was the control (the feed was not given additional S. fusiformis flour. Meanwhile, the P1, P2, and P3 groups were fed with the addition of S. fusiformis flour at different concentrations (1%, 3%, and 5%). Koi fish were reared for 30 days by observing the color brightness level which was measured once every 7 days using the Toca Color Finder (TCF). Survival rate was measure at the end of the study. The results showed the survival rate of koi fish was 100%, the highest growth rate was found in the addition of Spirulina flour with a dose of 3% of 1.15 ± 0.31%. osis 1% (P1) was able to increase the color of koi fish significantly compared to control (P0) with a final score of 24. The use of 1% spirulina (P1) did not show a different color improvement compared to P2 (score 22) and P3 (score 21) although the increase in color was higher than all treatments.